2015
DOI: 10.5740/jaoacint.15-008
|View full text |Cite
|
Sign up to set email alerts
|

The Monitoring of Triphenylmethane Dyes in Aquaculture Products Through the European Union Network of Official Control Laboratories

Abstract: Aquaculture has been the fastest growing animal production industry for the past four decades, and almost half of the fish eaten in the world are now farmed fish. To prevent diseases in this more intensive aquaculture farming, use of therapeutic chemicals has become a basic choice. The monitoring of malachite green, a triphenylmethane dye and one of the oldest and widely used chemicals in fish production, has gained more interest since the mid 1990s when this substance was finally proven to be toxic enough to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…The EURL, Anses-Foug eres (France), provides proficiency testing for National Reference Laboratories in charge of control for dye residues in aquaculture products with three rounds having been organised covering trout (2005,2009) and prawn (2013) samples (Verdon et al, 2015). The EURL, Anses-Foug eres (France), provides proficiency testing for National Reference Laboratories in charge of control for dye residues in aquaculture products with three rounds having been organised covering trout (2005,2009) and prawn (2013) samples (Verdon et al, 2015).…”
Section: Confirmatory Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The EURL, Anses-Foug eres (France), provides proficiency testing for National Reference Laboratories in charge of control for dye residues in aquaculture products with three rounds having been organised covering trout (2005,2009) and prawn (2013) samples (Verdon et al, 2015). The EURL, Anses-Foug eres (France), provides proficiency testing for National Reference Laboratories in charge of control for dye residues in aquaculture products with three rounds having been organised covering trout (2005,2009) and prawn (2013) samples (Verdon et al, 2015).…”
Section: Confirmatory Methodsmentioning
confidence: 99%
“…Several proficiency tests and interlaboratory studies have been reported for MG/LMG in fish. The EURL, Anses-Foug eres (France), provides proficiency testing for National Reference Laboratories in charge of control for dye residues in aquaculture products with three rounds having been organised covering trout (2005,2009) and prawn (2013) samples (Verdon et al, 2015). In January 2008, the Proficiency Test Advisory Board, Government Laboratory, Hong Kong reported on a proficiency test (APLAC T058) aimed at evaluating the testing capability of 48 participating laboratories in the quantitative analysis of MG and LMG in swamp eels; 48% and 62% of participants had satisfactory results (z-score ≤ 2) for the determination of MG (assigned value 28.2 lg/kg) and LMG (assigned value 2.21 lg/kg), respectively (Wong, 2008).…”
Section: Confirmatory Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For regulatory analysis, the method performance for MG, LMG, CV, LCV, and BG was characterized by decision limit and detectability (CCα and CCβ) at and below 0.5 μg/kg, trueness ranging from 100% to 110% recovery, and precision of 10% RSD. Alternative instrument parameters were additionally described for the identification of the LBG analyte in incurred trout by UHPLC-LTQ-Orbitrap TM -MS. 31 The method was included in several proficiency testing studies conducted by the EU Reference Laboratory for EU Member States 162 and was the method suggested in a recent Food Emergency Response Network proficiency test conducted by the USFDA for state and federal laboratories in the USA. In 2012, the method was established as AOAC First Action Method 2012.25 for future consideration as an AOAC Official Methods of Analysis.…”
Section: Procedures To Extract and Analyze Triphenylmethane Dye Residmentioning
confidence: 99%